Improving cellular uptake and bioavailability of periplocymarin-linoleic acid prodrug by combining PEGylated liposome - Huiyun Zhang; Shunru Wei; Yu Zhang; Anran Pan; Michael Adu-Frimpong; Congyong Sun; Gang Qi (Taylor & Francis Group, 2022)
Periplocymarin (PPM), a cardiac glycoside isolated from Cortex periplocae, has a strong anti-tumor effect against various cancer cells. However, cardiotoxicity and rapid metabolism hinder its clinical applications. In this study, small molecule prodrug was integrated into PEGylated liposome to improve the efficiency of periplocymarin in vivo. The periplocymarin-linoleic acid (PL) prodrug was constructed by conjugating the linoleic acid with PPM via esterification, which was further facilitated to form PEGylated liposome (PL-Lip) through film dispersion. Compared with PL self-assembling nano-prodrug (PL-SNP), PL-Lip showed better colloid stability, sustained drug release kinetics, and enhanced cellular uptake by tumor cells. Notably, PL-Lip performed better than PPM and PL-SNP in terms of tumor distribution and pharmacokinetics, which include bioavailability and half-life. Altogether, the prodrug PEGylated liposome represents a good strategy and method for long-circulating and tumor-targeting delivery of periplocymarin with enhanced clinical application prospect.